Genome-Wide Characterization and Expression Analysis Provide Basis to the Biological Function of Cotton FBA Genes - Li, Zhong-Qing; Zhang, Yao; Li, He; Su, Ting-Ting; Liu, Cheng-Gong; Han, Zi-Chao; Wang, Ai-Ying; Zhu, Jian-Bo (Frontiers in Plant Science, 2021)
Fructose-1,6-biphosphate aldolase (FBA) is a multifunctional enzyme in plants, which participates in the process of Calvin-Benson cycle, glycolysis and gluconeogenesis. Despite the importance of FBA genes in regulating plant growth, development and abiotic stress responses, little is known about their roles in cotton. In the present study, we performed genome-wide identification and characterization of FBAs in Gossypium hirsutum. Totally seventeen GhFBA genes were identified. According to the analysis of functional domain, phylogenetic relationship, and gene structure, GhFBA genes were classified into two subgroups. Furthermore, nine GhFBAs were predicted to be in chloroplast and eight were located in cytoplasm. Moreover, the promoter prediction showed a variety of abiotic stresses and phytohormone related cis-acting elements exist in the 2k up-stream region of GhFBA. And the evolutionary characteristics of cotton FBA genes were clearly presented by synteny analysis. Moreover, the results of transcriptome and qRT-PCR analysis showed that the expression of GhFBAs were related to the tissue distribution, and further analysis suggested that GhFBAs could respond to various abiotic stress and phytohormonal treatments. Overall, our systematic analysis of GhFBA genes would not only provide a basis for the understanding of the evolution of GhFBAs, but also found a foundation for the further function analysis of GhFBAs to improve cotton yield and environmental adaptability.